Состояние эндогенной интоксикации организма детей с множественным кариесом зубов на фоне заболеваний желудочно-кишечного тракта = State of endogenous intoxication in children with multiple caries in the course of gastrointestinal tract diseases - E. J. Dyachuk (Kazimierz Wielki University, 2015)
Dyachuk E. J. Состояние эндогенной интоксикации организма детей с множественным кариесом зубов на фоне заболеваний желудочно-кишечного тракта = State of endogenous intoxication in children with multiple caries in the course of gastrointestinal tract diseases. Journal of Education, Health and Sport. 2015;5(6):267-272. ISSN 2391-8306. DOI 10.5281/zenodo.18564 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A267-272 https://pbn.nauka.gov.pl/works/566002 http://dx.doi.org/10.5281/zenodo.18564 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 14.06.2015.     Состояние эндогенной интоксикации организма детей с множественным кариесом зубов на фоне заболеваний желудочно-кишечного тракта State of endogenous intoxication in children with multiple caries in the course of gastrointestinal tract diseases Дячук Э. Й. Dyachuk E. J. Ужгородский национальный университет, Ужгород, Украина (88000, Украина, Закарпатская обл., Ужгород, пл. Народная, 3) Кафедра детской стоматологии, ассистент кафедры Uzhgorod National University, Uzhgorod, Ukraine (88000, Ukraine, Transcarpathian region, Uzhgorod, People's square, 3) Department of Pediatric Dentistry e-mail: khoma.edita@rambler.ru   Резюме В статье, на основании обследования 125 детей, доказано, что у школьников с множественным кариесом на фоне поражений ЖКТ более выраженная эндогенная интоксикация организма, чем у стоматологически и соматически здоровых детей, что может обусловливать более высокую частоту и интенсивность кариозного процесса и его осложнений.   Ключевые слова: дети, заболевания желудочно-кишечного тракта, кариес зубов, эндогенная интоксикация.   Summary An article presets data, based on examination of 125 children, it is proved that pupils with multiple caries in the course of digestive tract diseases has more pronounced endogenous intoxication of organism, than in dental and somatic healthy children, it could cause more increased frequency and intensity of caries process and its complications.   Key words: children, disease of the gastrointestinal tract, caries of teeth, endogenous intoxication.